POSSIBLE URANIUM SOURCES FOR THE LARGEST URANIUM DISTRICT ASSOCIATED WITH VOLCANISM: THE STRELTSOVKA CALDERA (TRANSBAIKALIA, RUSSIA) - Chabiron A.; Cuney M.; Poty B. (My University, 2003)
The uranium deposits of the Late Jurassic Streltsovka caldera (Transbaikalia, Russia) represent the largest uranium field associated with volcanics in the world (280,000 t U) and Russia's largest uranium resources. About one third of the caldera stratigraphic pile consists of rhyolites which are strongly altered. The rhyolitic magma preserved as melt inclusions in quartz phenocrysts corresponds to a mildly peralkaline melt (1.04<Na+K/Al<1.10), rich in F (1.4-2.7 wt%) and U (15-23 ppm). Fission track distribution shows that U is almost exclusively located in the matrix of the rhyolites. Mass balance calculations demonstrate that the amounts of U and F leached from the rhyolites (26,000 t U and 52 Mt F per km3) may greatly exceed the amounts of U and F concentrated in the known U and F ore deposits of the Streltsovka caldera. The magmatic fluids expelled from the Streltsovka rhyolitic melts probably contained less than 1 ppm U, according to the low KDfluid/melt of uranium for such F-rich peralkaline melts. Thus, the mass of uranium released by the exsolution of the volatile phase from the extruded rhyolitic melts was of minor importance, in the range of a few 1,000 t U. The Hercynian biotite granites which represent the major part of the caldera basement belong to a sodic-potassic subalkaline magmatic association. An alkaline biotite leucogranite was only identified in the deepest part of the drillings. The pervasive and intensive hydrothermal alteration of U-bearing accessory minerals in the granites shows that uranium was also extracted from these granites. Mass balance calculations for the granites show that zircon and apatite are minor hosts for U and Th compared to thorite and allanite. The alteration of allanite to monazite and REE carbonate may have liberated up to 1,638 t U/km3 of granite. Beside the efficiency of hydrothermal alteration, the exceptionally large uranium resources of the Streltsovka caldera, compared to other volcanic-related uranium districts in the world, appear to result from the juxtaposition of two major uranium sources: highly fractionated peralkaline rhyolites of Jurassic age in the caldera, and U-rich subalkaline granites of Variscan age in the basement in which the major uranium-bearing accessory minerals were metamict at the time of the hydrothermal ore formation.
Keywords: Uranium; Streltsovka; Rhyolite; Granite; Russia; Mesozoic::Jurassic::Upper; Мезозой::Юрская::Верхний